2016
DOI: 10.7324/japs.2016.60904
|View full text |Cite
|
Sign up to set email alerts
|

Formulation Development of Solid Dispersions of Bosentan using Gelucire 50/13 and Poloxamer 188

Abstract: The objectives of the present research work are to improve the solubility and dissolution rate of bosentan. Solid dispersions of bosentan were prepared by fusion method by using two selected hydrophilic meltable carriers visà-vis gelucire 50/13 and poloxamer 188. Sylysia 350 was used as an adsorbent. Solid dispersions were evaluated for solubility, phase solubility, flowability, compressibility, Fourier transform infrared spectra (FT-IR), differential scanning calorimetry (DSC). Solubility studies showed 8 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 18 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…Several surfactants such as Inulin [69,70], inutec [70], poloxamer 407 [71], Gelucire 44/14 [72], and Compritol 888 ATO [73] are used in preparation of SD. In a study by Panda et al [74], Gelucire 50/13 and poloxamer 188 were used in the development of a bosentan SD formulation to improve the solubility and dissolution of this drug. The results showed that the solubility of bosentan from the SD formulation increased 8- and 10-fold when using Gelucire 50/13- and poloxamer 188-based SDs, respectively, in comparison with that of the pure drug.…”
Section: Solid Dispersionsmentioning
confidence: 99%
“…Several surfactants such as Inulin [69,70], inutec [70], poloxamer 407 [71], Gelucire 44/14 [72], and Compritol 888 ATO [73] are used in preparation of SD. In a study by Panda et al [74], Gelucire 50/13 and poloxamer 188 were used in the development of a bosentan SD formulation to improve the solubility and dissolution of this drug. The results showed that the solubility of bosentan from the SD formulation increased 8- and 10-fold when using Gelucire 50/13- and poloxamer 188-based SDs, respectively, in comparison with that of the pure drug.…”
Section: Solid Dispersionsmentioning
confidence: 99%
“…As a result, they tend to have a poor flow, poor compressibility, and hard to pulverize [99,100]. To resolve these problems, inert material with good flow and compressibility should be used to absorb the dispersion on its surface [101]. Moreover, adsorption carriers not only prevent the crystal growth due to confined space within the pores of carriers but also stabilize the drug in the TSD by various chemical interactions [102].…”
Section: Adsorbentsmentioning
confidence: 99%
“…Poloxamers are nonionic surfactant, polyoxyethylenepolypropylene block copolymer consists of hydrophilic core (ethylene oxide) and hydrophobic core (polypropylene oxide) blocks arranged in a triblock structure resulting in an amphiphilic copolymer 17 . Poloxamers are hydrophilic non-ionic surfactant used mainly as solubilizing agents, wetting agents and used for enhancing the solubility and bioavailability of poorly soluble drugs [18][19] .…”
Section: Introductionmentioning
confidence: 99%